2018
DOI: 10.1108/rpj-05-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exposure time on energy consumption and mechanical properties of SLM fabricated parts

Abstract: Purpose Many process parameters in selective laser melting (SLM) can be configured to optimize build time, which directly relates to energy consumption, and to achieve acceptable part quality. This study aims to investigate whether energy can be effectively reduced with acceptable mechanical properties. The influence of exposure time is primarily focused to correlate energy consumption to mechanical properties. Design/methodology/approach Through single-factor design and experiment result analysis, three lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Optimizing process parameters is an effective technique to realize energy-effective manufacturing. For other AM systems, SLM has been studied in depth for energy consumption and part quality based on experiments (Zhu et al, 2019b;Peng et al, 2018b). It was found that improving the part quality with an incensement in the electrical energy consumption differs greatly, which is in line with our work.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Optimizing process parameters is an effective technique to realize energy-effective manufacturing. For other AM systems, SLM has been studied in depth for energy consumption and part quality based on experiments (Zhu et al, 2019b;Peng et al, 2018b). It was found that improving the part quality with an incensement in the electrical energy consumption differs greatly, which is in line with our work.…”
Section: Discussionsupporting
confidence: 86%
“…Both energy consumption and surface roughness can be optimized by controlling layer thickness for SLS (Strano et al, 2012), which is in line with our work. However, saving electrical energy to obtain an acceptable tensile strength is not recommended in SLM, which was different in SLA (Zhu et al, 2019b;Peng et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of great importance to investigate the effect of process parameters on material thermal behaviour based on numerical simulation. At present, the numerical simulation research on the influence of parameterization of SLM is mainly about continuous SLM, and there are few reports on pulse-laser SLM, where all powder will experience the irradiation of the laser centre for a continue SLM system, while part of powder experiences the irradiation of the laser centre for a pulse-laser SLM system whose manufacturing process is that laser scans powder discontinuously, point by point [5]. Ahmed Hussein et al conducted a finite element simulation of the temperature fields in single layers in SLM and suggested that the predicted length of the molten pool increases at higher scan speed [6].…”
Section: Introductionmentioning
confidence: 99%